2020
DOI: 10.3389/fphar.2020.00466
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of DiDang Tang Against AlCl3-Induced Oxidative Stress and Apoptosis in PC12 Cells Through the Activation of SIRT1-Mediated Akt/Nrf2/HO-1 Pathway

Abstract: Aluminum (Al) is considered a pathological factor for various neurological and neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD). The neurotoxicity of aluminum can cause oxidative brain damage, trigger apoptosis, and ultimately cause irreversible damage to neurons. DiDang Tang (DDT), a classic formula within traditional Chinese medicine for promoting blood circulation and removing blood stasis and collaterals, is widely used for the treatment of stroke and AD. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The extracellular-signal-regulated kinase (ERK) forms a signaling pathway together with Nrf2 [100,101], as does AMPK with Nrf2 [102]. Sirtuin-1 and Nrf2 represent another joint pathway induced by phytochemicals [103].…”
Section: Phytochemicals and Health-a Broader Perspectivementioning
confidence: 99%
“…The extracellular-signal-regulated kinase (ERK) forms a signaling pathway together with Nrf2 [100,101], as does AMPK with Nrf2 [102]. Sirtuin-1 and Nrf2 represent another joint pathway induced by phytochemicals [103].…”
Section: Phytochemicals and Health-a Broader Perspectivementioning
confidence: 99%
“…Currently, aluminum has been reported as an inducer of oxidative stress leading to the appearance of AD markers, so that it has been used to develop rat models of AD (Almuhayawi et al, 2020;Ogunlade et al, 2020). It is also reported that AlCl 3 -induced oxidative stress can lead to apoptosis in PC12 cells (Lu et al, 2020). In this regard, elevated oxidative stress in neurons reduces endogenous antioxidant enzymes such as catalase (CAT), glutathione peroxidase 1 (GPX), and superoxide dismutase 1 (SOD), and there was an increase in activity and levels of iNOS, which in turn produces higher levels of ROS (Guo et al, 2005;Sharma and Mishra, 2006;Sadauskiene et al, 2018;Kinawy, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…8 We also found that the protective effect of Di Dang decoction against AlCl 3-induced oxidative stress and apoptosis in PC12 cells through the activation of SIRT1-Mediated Akt/Nrf2/HO-1pathway. 9 In addition, previous reports showed that leech alcohol extract and rhubarb water extract alleviated the inflammation of peripheral tissue and cerebral edema in rats with ICH. 10,11 Peach seed water extract up-regulated VEGF and VEGF receptor 2 after ICH in a mouse model 6 and inhibited glucose deprivation injury in PC12 cells.…”
Section: Purposementioning
confidence: 96%
“…As our team reported, 8,9 we have established a method for the detection of active ingredients from DDD via highperformance liquid chromatography (HPLC, Agilent, Santa Clara, CA, US). Eighteen major peaks of DDD extract were identified using HPLC.…”
Section: Animal Maintenancementioning
confidence: 99%